PENGEMBANGAN POTENSI GURU MGMP PPKn SMP KOTA KEDIRI DALAM PEMBUATAN MODUL AJAR - Sasmita, Wikan; Nursalim, Nursalim; Widodo, Agus; Anyastuti, Etty; Suratman, Suratman; Pristiani, Yunita Dwi; Wiranata, Irawan Hadi (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
The development of the potential of MGMP PPKn SMP Kediri teachers is accompanied by the development of the era of disruption, this era will require teachers to innovate in the independent curriculum, especially in making teaching modules. The increasingly severe challenges must improve competence in learning. Through teacher potential development activities carried out by PPKn FKIP UNP Kediri lecturers through service to the community with harpan can improve competence in making teaching modules. This study is to describe and analyze the impact of developing the potential of MGMP PPKn SMP Kediri teachers in making teaching modules. Qualitative approach with the type of case study on MGMP PPKn SMP Kediri city teachers. The process of collecting interview data, observation, documentation. Analysis techniques with conclusions. Validity checking with extended presence of researchers and triangulation. The results show an increase in competency in making teaching modules.